Twentieth Century Islamic Thought and the Challenges of Modernity (A Study of the Perspective of Bediuzzaman Said Nursi) - Hafiz Abdul Ghani (Pakistan Journal of Islamic Research, 2019)
In this article I have discussed the nature of socio-religious challenges that modernity has brought to the contemporary world, its particular impact on the Muslim societies and how the Islamic thinkers suggested to cope with the modern challenges in 20th century. It is a study of the methodology of Said Nursi. Said Nursi (1877-1960) also known as Bediuzzaman is a very prominent Turkish religious intellectual who made untiring struggle to deal with the challenges of modernity in modern Turkey. Modernity is a complex phenomenon which has had manifold effects and side-effects on contemporary societies. The real challenge before the Islamic intellectuals of 20th century was to decide how to deal with modernity especially the newly ascendant mentality (within the Muslim societies) that want to uproot Islam and eradicate its practices in the name of progress and prosperity. For Said Nursi there were two options: (1) Lead a political resistance against modern secular forces, or (2) Adopt a non-violent way of empowering individuals by strengthening faith. Said Nursi realized that the second option was the best way to fortify Islamic faith and practices. This study furthermore examines the scope of the application of Said Nursi’s methodology across the Muslim world.